DEVELOPMENT OF DEMULSIFIER FOR MALAYSIAN CRUDE OIL - CHANDRAN, KRITTIKA (2016)
Crude oil is always produced with water. This causes many problems during oil production, arising from the formation of emulsion. Emulsion is a mixture of liquids with no mutual solubility between them. To overcome this issue, demulsifiers are formulated to break the emulsion. Demulsifier main function is to reduce the interfacial tension properties of the emulsion. The main objective of this study is to formulate a suitable demulsifier for Malaysian crude oil. In order to formulate a suitable demulsifier, it is important to determine the physical properties of the crude oil as the demulsification formulation is dictated by the properties of the crude oil. Two types of emulsion which r.re. the FOR errmlgjrm (rmrlp A) and natural Ptrmlsinn (Crude B) was studied. EOR emulsion is the crude with surfactant-polymer (SP) in the injection water. The combination of these three components are the next generation technology designed to provide tolerance to extreme salinity and also produces higher mobility control in the EOR crude.